Copyright Protection of Video Game for Game Developer in Indonesia - JUANDA MARIA ANGELIA; ANNISA AYU MULIA; DETANTI ASMANINGAYU PRAMESTI (Fakultas Hukum Universitas Airlangga, 2019)
This study aimed to firstly, analyze the frequent infringements related to copyright of video games, as well as the legal protection for game developers who create video games. Secondly, to determine the factors that impede the copyright protection of video games in Indonesia. This research employs empirical approach or sociolegal, with library research and field studies to collect data. In the literature, the author uses the legal resources to support the analysis. The study was based primarily on Law no. 28 of 2014 regarding Copyright. In the field study, the author interviewed several game developers in Indonesia, as well as the practitioner from Directorate General Intellectual Property Right Jakarta and academician from Faculty of Law Universitas Gadjah Mada. Analysis of the research was conducted using qualitative data analysis, with the results compiled by descriptive-analysis to achieve the research objectives. Results of this study indicates that the laws and regulations of Indonesia has virtually provided legal protection for game developers as the creator of the video game, but there are still uncertainties in settings, such as obscurity any part of the video game that is protected by the copyright laws of Indonesia, considering that the video game consists of several constituent.